CHARACTERIZATION OF COAT PROTEIN (CP) GENE OF SUGARCANE MOSAICVIRUS (SCMV) FROM ISOLATES OF PAKISTAN AND ITS PHYLOGENETIC RELATIONSHIPS - S. Akbar; M. Tahir1 and S. Afghan (Journal of Animal and Plant Sciences, 2017)
Sugarcane (Saccharum officinarium, family Poaceae) is a widely grown cash crop in Pakistan. Pakistan is the fifth largest country in the world in terms of area under sugarcane cultivation, 11th by production and 60th in yield. Mosaic is amongst the major diseases of sugarcane in the country, which causes decline in cane yield in the range of 10-32% and in sugar yield in the range of 6-10%. Thirty two (32) sugarcane leaf samples, showing mosaic symptoms, and five asymptomatic leaf samples were collected from Punjab and Khyber Pakhtun Khwa (KPK) provinces of Pakistan during 2013-2014. RNA was extracted and subjected to PCR amplification using a universal set of coat protein (CP) gene primers. An expected size band (~1.2kb) was obtained from all symptomatic leaf samples. Amplified products were T/A cloned and sequenced in both orientations. The available CP sequences of 20 samples were ranged between 890-938bp in length which showed 95-100% nucleotide sequence identities among them and 85-100% nucleotide sequence identity with the rest of CP sequences from world while shared highest nucleotide sequence identity (98% over the stretch of ~900bp) to an isolate of Sugarcane mosaic virus (SCMV; accession number DQ648195). The sequence analysis of present study CP isolates and their phylogenetic relationships with the rest of world are discussed in the manuscript.
Keywords: Potyviridae; Sugarcane mosaic virus; Coat protein; Phylogenetic; Diversity